2004
DOI: 10.1080/10739680490517677
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of α4 and αL Integrins to IL‐4‐Induced Leukocyte Rolling and Adhesion

Abstract: Following tissue activation with IL-4, alpha4 and alphaL initiate the attachment and deceleration, respectively, of leukocytes during rolling, and are responsible for mediating the adhesion CD4+, CD8+, Gr-1+ leukocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…pI and prevents the attachment of HL-60 cells; from the.endothelium in vitro (23); Some studies 'demonstrated a correlation between high expression' of CD49d and metastasis (24; 25). The upregulation of VLA-4 expression increases the cell interaction with the blood vessels (26). Thus, the reduced expression of CD49d suggests the beneficial effect of histamine in immunotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…pI and prevents the attachment of HL-60 cells; from the.endothelium in vitro (23); Some studies 'demonstrated a correlation between high expression' of CD49d and metastasis (24; 25). The upregulation of VLA-4 expression increases the cell interaction with the blood vessels (26). Thus, the reduced expression of CD49d suggests the beneficial effect of histamine in immunotherapy.…”
Section: Discussionmentioning
confidence: 98%
“… 39 Alternatively, the IL-4-mediated inhibition of CD49d expression in HaCaT keratinocytes could be a mechanism to downregulate leukocyte adhesion to keratinocytes to control the inflammatory process, since CD49d is known to play a critical role in leukocyte adhesion to other cell types. 40 This phenomenon may also reflect a mechanism by which the keratinocyte response to locally released IL-4 attempts to control excessive inflammatory processes such as AD.…”
Section: Discussionmentioning
confidence: 99%
“…The necessity of both integrins, LFA‐1 and VLA‐4, for leukocyte adhesion and spreading in vivo has been demonstrated in an interleukin‐4‐induced inflammation model ( 50 ). Firm adhesion and spreading of monocytes on the surface of the endothelium requires functional LFA‐1 and VLA‐4 binding to their receptors ICAM‐1 and VCAM‐1 expressed on activated endothelium ( 50 ). In fact, during diapedesis leukocytes form integrin‐mediated adhesions at their leading edge while co‐ordinately disassembling integrin assemblies at their rear, which has been shown to be regulated by chemokines ( 51,52,53 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the formation of atherosclerotic plaques, macrophages accumulate in the tunica intima of vessels as a consequence of diapedesis of peripheral blood monocytes ( 49 ). The necessity of both integrins, LFA‐1 and VLA‐4, for leukocyte adhesion and spreading in vivo has been demonstrated in an interleukin‐4‐induced inflammation model ( 50 ). Firm adhesion and spreading of monocytes on the surface of the endothelium requires functional LFA‐1 and VLA‐4 binding to their receptors ICAM‐1 and VCAM‐1 expressed on activated endothelium ( 50 ).…”
Section: Discussionmentioning
confidence: 99%